Juridical Analysis Of The Authority Of Quarantine Investigators In Handling Cases Of Animal Entry That Have Exceeded The Entry and Exit Points In Batam City: Research Study At The Quarantine Of Animals, Fish, And Plants Office In The Riau Archipelago At Hang Nadim And Telaga Punggur Service Units - Edy Chandra Zebua; Dahlan Dahlan; Sayid Fadhil; Soerya Respationo; Erniyanti Erniyanti (International Journal of Law, Crime and Justice, 2024)
Violations of quarantine regulations in Batam City continue to occur to this day. Despite the enactment of Law No. 21 of 2019 concerning Animal, Fish, and Plant Quarantine, which replaced Law No. 16 of 1992 on the same subject and introduced stricter criminal sanctions for violations, there has still not been a deterrent effect on those bringing prohibited items without meeting quarantine requirements. This research addresses how the authority and implementation of quarantine investigators' powers are regulated in handling cases of animal entry that have bypassed the designated import and export points in Batam City, what obstacles or challenges quarantine investigators face, and the solutions at the Animal, Fish, and Plant Quarantine Office of the Riau Archipelago at the Hang Nadim and Telaga Punggur Service Units. The research method combines normative legal research with empirical sociological approaches, utilizing both inductive and deductive methods to analyze and clarify the relationship between research variables and the research object. This approach aims to provide a comprehensive understanding that benefits readers, particularly future researchers and academics. The findings reveal ongoing uncertainty among quarantine investigators in enforcing quarantine regulations in Batam City. This issue arises from differing interpretations of Law No. 21 of 2019 among quarantine officers and the shortage of human resources, which affects investigators' focus on legal enforcement actions, including criminal sanctions. In Batam City, the resolution of quarantine regulation violations prioritizes the philosophy of "ultimum remedium" where punishment is seen as a last resort. Administrative sanctions for quarantine violations include quarantine detention, rejection, and/or destruction of the violating items.